2016
DOI: 10.1002/anie.201605429
|View full text |Cite|
|
Sign up to set email alerts
|

Engineered Substrate‐Specific Delta PKC Antagonists to Enhance Cardiac Therapeutics

Abstract: Most protein kinases phosphorylate multiple substrates, each of which induces different and sometimes opposing functions. Determining the role of phosphorylation of each substrate following a specific stimulus is a challenge but is essential to elucidate the role of that substrate in the signaling event. Here we describe a rational approach to identify inhibitors of delta protein kinase C (δPKC), each inhibiting the phosphorylation of only one of δPKC’s substrates. δPKC regulates many signaling events and we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…We have previously shown that two proteins that interact usually share short sequences of homology that represent sites of both inter- and intra-molecular interactions 17,23,24 . More recently, we described a similar rational approach to develop PKC inhibitors that selectively block interaction and phosphorylation of only one protein substrate of these multi-substrate kinases 6,7,25 . Using the same approach, we rationally designed SAMβA.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that two proteins that interact usually share short sequences of homology that represent sites of both inter- and intra-molecular interactions 17,23,24 . More recently, we described a similar rational approach to develop PKC inhibitors that selectively block interaction and phosphorylation of only one protein substrate of these multi-substrate kinases 6,7,25 . Using the same approach, we rationally designed SAMβA.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that δPKC is a key mediator of IR injury, and the inhibition of δPKC activity, with the pan-inhibitor peptide δV1-1, at the time of reperfusion attenuates injury in animal models of IR, and in patients with acute myocardial infarction [ 8 , 9 ]. δPKC has multiple substrates with various, and often opposing, downstream effects [ 10 , 32 ]. cTnI is known to be phosphorylated by δPKC in IR [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of δPKC during reperfusion induces cell death through the dysregulation of mitochondrial function, apoptosis, and oncosis; a δPKC pan-inhibitor designed in our lab (δV1-1) mitigated myocardial injury by more than 60% in preclinical models of IR injury, and in patients with acute myocardial infarction [ 8 , 9 ]. δPKC has multiple phosphorylation targets in IR, regulating cellular metabolism and mitochondrial function, with overlapping, and often opposing, downstream effects, as exemplified by a set of substrate-specific δPKC inhibitors developed in our lab to delineate these effects [ 10 ]. Among its targets, δPKC phosphorylates cTnI at serine 23/24, serine 43/45, and threonine 144, and we have previously shown that phosphorylation of cTnI by δPKC increases with IR, and cTnI phosphorylation by δPKC is thought to cause a reduction in maximal myofilament force in cardiomyocytes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peptide inhibitors derived from docking sites and docking motifs have also been developed for the MAPK family of kinases [ 6 ]. Recently, Qvit et al demonstrated the substrate-specific phosphorylation inhibition by PKCδ using peptides of predicted docking motifs of MARCKS, Drp1, and IRS1 [ 26 ]. We anticipated that DM peptides of MYPT1 act as MYPT1-specific inhibitors against Rho-kinase.…”
Section: Discussionmentioning
confidence: 99%